Implementação em FPGA de módulo de efeito de reverberação - Nascimento, Diego Vinícius Cirilo do (2014)
Reverberation is caused by the reflection of the sound in adjacent surfaces close to the sound source during its propagation to the listener. The impulsive response of an environment represents its reverberation characteristics. Being dependent on the environment, reverberation takes to the listener characteristics of the space where the sound is originated and its absence does not commonly sounds like “natural”. When recording sounds, it is not always possible to have the desirable characteristics of reverberation of an environment, therefore methods for artificial reverberation have been developed, always seeking a more efficient implementations and more faithful to the real environments. This work presents an implementation in FPGAs (Field Programmable Gate Arrays ) of a classic digital reverberation audio structure, based on a proposal of Manfred Schroeder, using sets of all-pass and comb filters. The developed system exploits the use of reconfigurable hardware as a platform development and implementation of digital audio effects, focusing on the modularity and reuse characteristics